Differential Chloride Secretory Capacity in Transepithelial Ion Transport Properties in Chronic Rhinosinusitis. Issue 6 (November 2020) - McCormick, Justin; Hoffman, Kyle; Thompson, Harrison; Skinner, Daniel; Zhang, Shaoyan; Grayson, Jessica; Illek, Beate; Cho, Do-Yeon; Woodworth, Bradford A.
Background: Epithelial ion transport regulates hydration of airway mucosal surfaces, and thus promotes effective mucociliary clearance (MCC). Decreased transepithelial Cl − transport may contribute to epithelial dysfunction by abrogating MCC and increasing mucus viscosity in chronic rhinosinusitis (CRS). The objective of the current study is to evaluate Cl − channel transport properties from cultures of human sinonasal epithelia. Methods: Human sinonasal epithelia (HSNE) from patients undergoing sinus surgery were cultured at an air-liquid interface to confluence and full differentiation. The epithelial monolayers were mounted in Ussing Chambers to investigate pharmacological manipulation of ion transport. Epithelial Na + channel (via Amiloride), CFTR (via forskolin), and Ca 2+ -activated Cl − channel (CaCC, via UTP) transport were investigated among three different patient groups: Control, CRS and CRS with polyposis. CFTR mRNA levels were evaluated with quantitative RT-PCR. Results: HSNE cultures from 18 patients (Control = 9, CRS = 6, CRS with polyposis = 3) were evaluated in 142 experiments. Summary data from the 18 patients demonstrated that stimulated CFTR-mediated anion transport (Δ ISC ) was significantly lower with CRS (7.58+/−2.24 µA/cm 2 ) compared to control (25.86+/−3.44 µA/cm 2 ) and CRS with polyposis (20.16+/−4.0 µA/cm 2 ) (p = 0.004). No statistically significant difference was found for CaCC anion transport between groups (p = 0.39). Significantly decreased mRNA (relative expression) was noted in CRS cultures (CRS = 40.83+/−1.76 vs. control = 116.2+/−24.27, p = 0.03). Conclusions: A substantial decrease in the Cl − secretory capacity of HSNE monolayers was demonstrated in CRS subjects. Data suggest that CFTR may contribute more to abnormal ion transport in CRS than CaCC.